Challenges and Perspective of Recent Biomass Pretreatment Solvents - Kim, Kwang Ho; Yoo, Chang Geun (Frontiers in Chemical Engineering, 2021)
Biomass pretreatment has been investigated and applied to several biorefinery processes for past decades. The increased demands on renewable and sustainable products require enhancing the current conversion efficiency and expanding the utilization of biomass from a single component (i.e., cellulose) to entire biomass components, including hemicellulose and lignin. Especially, innovations in biomass characterization and conversion technologies reveal many fundamental questions and propose a new paradigm in biorefinery processes. Although practical biomass utilization still has many limitations and challenges, such as feedstock variety, valorization of non-cellulose components, and eco-friendliness of the applied catalyst and solvent, advancements in pretreatment solvents can be a key for overcoming these technical, economic and environmental obstacles. This mini review introduces recent developments in biomass pretreatment